Vegetation restoration of abandoned cropland improves soil ecosystem multifunctionality through alleviating nitrogen-limitation in the China Danxia - Wang, Chao; Yang, Qiannan; Zhang, Chi; Zhang, Xiaolong; Chen, Jing; Liu, Kexue (Frontiers in Plant Science, 2023)
The microbial requirement for nutrient resources can be estimated by soil extracellular enzyme stoichiometry (EES) and their stoichiometries. Implementing the Grain for Green Program has significantly impacted land use and soil nutrient management in the China Danxia. However, drivers of soil microbial nutrient limitation changes in abandoned cropland (AC) remained unclear after vegetation restoration. Here, according to vector analysis, we evaluated microbial nutrient limitation by studying soil EES across vegetation restoration types (naturally restored secondary forests (NF) and artificially planted forests (AF)) with AC as a control. Results showed both NF and AF soils averaged higher C- and P- acquiring enzyme, indicating rapid C and P turnover rates after vegetation restoration. However, vegetation restoration resulted in higher C requirement for microorganisms with higher enzyme C:N and vector length. In addition, microorganisms shifted from N- (< 45°) to P-limited (> 45°) conditions with enzyme N:P less than 1 after vegetation restoration, and NF exacerbated microbial P limitation compared to AF. Decreased N limitation following vegetation restoration could be contributed to improving soil ecosystem multifunctionality. The greater variation of EES was explained by the interaction of pH, soil nutrient, and microbial biomass than by any one of these factors alone, suggesting that both abiotic and biotic factors regulate microbial nutrient limitation and microbial process. Overall, our results revealed vegetation restoration could alleviate N limitation in the China Danxia, and thus enhance soil ecosystem by regulating lower microbial N limitation, which provide insight into nutrient management strategies under ecological restoration of degraded areas.